GEOCHEMICAL MAPPING AND ENVIRONMENTAL INDEXING OF AN URBAN AREA (RIO GRANDE, RS) - Nicolai Mirlean; Mariana Luiza Ribeiro Gripp (Geochimica Brasiliensis, 2018)
We have carried out a geochemical mapping of soil cover of industrial and residential sectors of the city of Rio Grande (RS). Various anomalous zones of mercury, copper, zinc, lead, nickel, chromium and iron have been identified, which corresponded to the historic-spatial allocation of different industries in the city. The mapping of the city's territory using the complex eco-geochemical index Zc demonstrated that most of the urban area is contaminated with metals up to the level requiring mandatory mitigation measures. The application of the method of sequential subtraction from the complex index of elements by the degree of their participation in the contamination of the territory made it possible to establish a paragenetic association of metals Cu, Pb, Zn, which forms the centers of metal contamination in the city. Based on the data received, an assessment of the pollution of the urban area was carried out in accordance with Brazilian legislation. This evaluation testified that studied soil belongs to Class 4 according to legislative norms, which means that the city needs immediate environmental management in terms of eliminating risks to human health and the environmental planning of future land use.